Ownership of Zakat Assets by their Recipients and its Effect on the Distribution of Zakat - el Gammal, Mohammad Mahmoud (Dirasat: Shari'a and Law Sciences, 2020)
The study aims to shed light on the difference of Jurists in the requirement of ownership of Zakat when distributed among the eight categories and to alert those in charge of distributing Zakat funds from non-governmental charitable associations and institutions on the importance of ownership to prevent the guardianship of those who deserve Zakat funds. The study used the mixed approach, which combines the inductive approach based on the careful tracking of the opinions of Jurists on the issue of Zakat ownership and their inferences, the analytical approach based on the analysis of opinions and sayings and their discussions, and the deductive approach based on applying the requirements of Zakat ownership on contemporary distribution issues. The study found that ownership means "transferring ownership of a thing to another", that is, giving the power and ability to dispose of the owned thing to the one who owns it. The relationship between the owner and the owned is a barrier to the conduct of others. The rights of the owner over the owned thing are to be able to use it and it is permissible for him to release usufruct and netting on it, and Ibn Arafah restricted "disposing" of everything that is permissible without anything else. Property rights are effects made by the street on the existence of grounds for repossession.